The Role of Supervisors in Improving Teachers' Ability to Implement the Class VI Fiqh Learning Process at Madrasah Ibtidaiyah Negeri 7 Langkat - Irda Novianti; Fuji Rahmadi; Bachtiar Siregar (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2022)
The role of supervisors increases the ability of teachers to carry out an integrated learning process in the implementation of the main tasks and functions of supervisors to provide guidance and guidance to teachers. The role of the supervisor is very much needed by the teacher in terms of assistance in preparing the administration of learning planning, the ability of the teacher in the process of implementing learning, the ability to assess learning outcomes, the ability to use media and learning resources, utilize the learning environment and resources, and use learning technology. The administration of fiqh learning planning consists of 10 points, namely annual programs, semester programs, syllabus, lesson plans, educational calendars, face-to-face schedules, daily agendas, list of grades, KKM and student attendance, and monitored through standard process supervision activities in madrasas once.